2017
DOI: 10.1123/ijspp.2016-0107
|View full text |Cite
|
Sign up to set email alerts
|

Similar Running Economy With Different Running Patterns Along the Aerial-Terrestrial Continuum

Abstract: Different running patterns were associated with similar RE. Aerial runners appear to rely more on elastic energy utilization with a rapid eccentric-concentric coupling time, whereas terrestrial runners appear to propel the body more forward rather than upward to limit work against gravity. Excluding runners with a mixed running pattern from analyses did not affect study interpretation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
46
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 28 publications
(56 citation statements)
references
References 31 publications
6
46
0
1
Order By: Relevance
“…In addition, having a low DF (short t c ) should promote an elastic behaviour; therefore, we hypothesized greater symmetry within contact and aerial phases compared with the DF high group. Moreover, a similar EC at endurance running speeds has been observed in runners exhibiting different running forms (Lussiana et al, 2017a). Therefore, despite these differences in running kinematics, we anticipated similar EC values at typical endurance speeds (i.e.…”
Section: Introductionsupporting
confidence: 64%
See 1 more Smart Citation
“…In addition, having a low DF (short t c ) should promote an elastic behaviour; therefore, we hypothesized greater symmetry within contact and aerial phases compared with the DF high group. Moreover, a similar EC at endurance running speeds has been observed in runners exhibiting different running forms (Lussiana et al, 2017a). Therefore, despite these differences in running kinematics, we anticipated similar EC values at typical endurance speeds (i.e.…”
Section: Introductionsupporting
confidence: 64%
“…Instead of decreasing t c to minimize EC, one effective strategy could be to increase t c to limit Δz and t a . Such a biomechanical strategy to optimize EC has been proposed recently under the name 'terrestrial running form' (Lussiana et al, 2017a), which resembles the grounded locomotive pattern used by some animal species (e.g. quail: Andrada et al, 2013) or the Groucho running style (McMahon et al, 1987).…”
Section: Introductionmentioning
confidence: 99%
“…Depending on speed, we have observed differences of 10% to 30% in t f of two different spontaneous running forms [7,8,9]. In these aforementioned studies, we have used a global subjective rating scale (named Volodalen ® scale) to classify runners into two main categories, based on scores along a continuum (V ® score).…”
Section: Introductionmentioning
confidence: 99%
“…In these aforementioned studies, we have used a global subjective rating scale (named Volodalen ® scale) to classify runners into two main categories, based on scores along a continuum (V ® score). Aerial runners (AER) favor vertical oscillations and longer t f as opposed to terrestrial runners (TER) who prefer propelling their body forward and use shorter t f [9]. These groups are termed VOL groups in what follows.…”
Section: Introductionmentioning
confidence: 99%
“…Here, we provide further evidence that the greater muscle forces in mid-/forefoot strikers are more economically produced due to the lower muscle contraction velocities and hence no difference in GM, GL or SOL metabolic energy consumption between foot strike patterns exist. Moreover, previous experimental research already demonstrated that differences in whole body metabolic energy consumption between foot strike patterns are small (Ogueta-Alday et al, 2014) or even non-existing (Cunningham et al, 2010; Gruber et al, 2013; Lussiana et al, 2017; Perl et al, 2012). Studies investigating the effect of gait retraining from rearfoot to forefoot strike running do not find an effect on the metabolic energy consumption during running when enough training sessions (?8) were offered (Ekizos et al, 2018; Roper et al, 2017).…”
Section: Discussionmentioning
confidence: 99%